THE ROLE OF PRELIMINARY EXPANSION OF SOFT TISSUES BEFORE GBR (World Bulletin of Public Health, 2022)
The deficiency of soft tissues observed in atrophy of the alveolar ridge creates certain difficulties for performing guided bone regeneration (GBR), the success of which to a certain extent depends on the closure of the wound without tension. The study examined the possibilities and the effect of preliminary expansion of soft tissues by an expander directly on microcirculation in the area of administration, and in general on the further results of the GBR.
Keywords: soft tissue expander; osteoplasty; bone atrophy; augmentation